Effect of Traverse Speed on Abrasive Waterjet Machining of Age Hardened Inconel 718 Nickel-Based Superalloy - Ay, Mustafa; Caydas, Ulas; Hascalik, Ahmet (Taylor & Francis Inc, 2010)
In this study, the effect of traverse speed on abrasive waterjet machining (AWJM) of Inconel 718 nickel-based superalloy was experimentally investigated. In the experiments, six different traverse speeds of 80, 130, 180, 230, 280, and 330 mm/min were employed. Following the tests, the surface roughness of the machined job, the kerf taper ratio, and kerf wideness were measured. The characteristics of machined surface were also investigated using scanning electron microscope (SEM) and atomic force microscope (AFM). As a consequence, it is observed that the surface roughness and kerf taper ratio tended to increase with traverse speed, while kerf wideness decreased.
Keywords: AFM; Age hardening; AWJ; Inconel 718; Traverse speed